Risk factors for locoregional recurrence in patients with resected N1 non-small cell lung cancer: a retrospective study to identify patterns of failure and implications for adjuvant radiotherapy - Fan, Chengcheng (BioMed Central, 2013)
BACKGROUND: Meta-analysis of randomized trials has shown that postoperative radiotherapy (PORT) had a detrimental effect on overall survival (OS) in patients with resected N1 non–small cell lung cancer (NSCLC). Conversely, the locoregional recurrence (LR) rate is reported to be high without adjuvant PORT in these patients. We have evaluated the pattern of failure, actuarial risk and risk factors for LR in order to identify the subset of N1 NSCLC patients with the highest risk of LR. These patients could potentially benefit from PORT. METHODS: We conducted a retrospective study on 199 patients with pathologically confirmed T1–3N1M0 NSCLC who underwent surgery. None of the patients had positive surgical margins or received preoperative therapy or PORT. The median follow-up was 53.8 months. Complete mediastinal lymph node (MLN) dissection and examination was defined as ≥3 dissected and examined MLN stations; incomplete MLN dissection or examination (IMD) was defined as <3 dissected or examined MLN stations. The primary end point of this study was freedom from LR (FFLR). Differences between patient groups were compared and risk factors for LR were identified by univariate and multivariate analyses. RESULTS: LR was identified in 41 (20.6%) patients, distant metastasis (DM) was identified in 79 (39.7%) patients and concurrent LR and DM was identified in 25 (12.6%) patients. The 3- and 5-year OS rates in patients with resected N1 NSCLC were 78.4% and 65.6%, respectively. The corresponding FFLR rates were 80.8% and 77.3%, respectively. Univariate analyses identified that nonsmokers, ≤23 dissected lymph nodes, visceral pleural invasion and lymph node ratio >10% were significantly associated with lower FFLR rates (P < 0.05). Multivariate analyses further confirmed positive lymph nodes at station 10 and IMD as risk factors for LR (P < 0.05). The 5-year LR rate was highest in patients with both these risk factors (48%). CONCLUSIONS: The incidence of LR in patients with surgically resected T1–3N1M0 NSCLC is high. Patients with IMD and positive lymph nodes at station 10 have the highest risk of LR, and may therefore benefit from adjuvant PORT. Further investigations of PORT in this subset of patients are warranted.